2020
DOI: 10.1111/bjd.19312
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive factors of unresponsiveness to omalizumab in patients with chronic spontaneous urticaria

Abstract: from the Cochrane Skin editorial base during the process of drafting the review. We thank Doreen Tushabe for participating in the protocol. The Cochrane Skin editorial base wishes to thank Laurence Le Cleach, Cochrane Dermatology Editor, for this review; the clinical referee Ignacio Garcia Doval; the consumer referee Liz Dale; and Heather Maxwell, who copy edited the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…5 Therefore, a lower peak concentration of omalizumab in CSU patients with a higher BMI may suggest a poorer response to omalizumab. Similar observations were reported in a retrospective study, where CSU patients with a BMI >30 kg/m 2 were linked to non-response to omalizumab treatment, 6 while an observational study linked severe CSU and high BMI to a poor response to omalizumab treatment. 7 In another study of patients with severe allergic asthma, it was also seen that non-responders to omalizumab had a significantly higher BMI (>30 kg/m 2 ) compared with responders.…”
Section: Omalizumab Serum Levels Predict Treatment Outcomes In Patien...supporting
confidence: 82%
“…5 Therefore, a lower peak concentration of omalizumab in CSU patients with a higher BMI may suggest a poorer response to omalizumab. Similar observations were reported in a retrospective study, where CSU patients with a BMI >30 kg/m 2 were linked to non-response to omalizumab treatment, 6 while an observational study linked severe CSU and high BMI to a poor response to omalizumab treatment. 7 In another study of patients with severe allergic asthma, it was also seen that non-responders to omalizumab had a significantly higher BMI (>30 kg/m 2 ) compared with responders.…”
Section: Omalizumab Serum Levels Predict Treatment Outcomes In Patien...supporting
confidence: 82%
“…Curto‐Barredo et al identified the body mass index (BMI) as a predictor of partial response to the 300 mg dose and better response with higher doses of omalizumab 21 . The role of a BMI >30 kg/m 2 as a factor linked to non‐response to omalizumab was confirmed by a very recent study 22 . Unfortunately, BMI was not included in our analysis as it was not present in our clinical records.…”
Section: Discussionmentioning
confidence: 71%
“…Table 5 summarizes the principal clinical and individual factors shown in previous studies to be associated with response to omalizumab and relapse after treatment withdrawal. 15,[18][19][20][21][22] As concerns previous investigations on the parameters examined in our analysis, a retrospective multicenter study demonstrated that baseline UAS7 was significantly correlated to the first but not to the second relapse, 18 The results of another study suggested that the long duration of CSU and history of angioedema may help predict the response to omalizumab, whereas no correlation was found with demographic data and other clinical variables examined in the analysis. 15 Curto-Barredo et al identified the body mass index (BMI) as a predictor of partial response to the 300 mg dose and better response with higher doses of omalizumab.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations